Refugee Women and Children: What can I Do?. Issue 5 (September 2016) - Callister, Lynn Clark
Abstract : Many of the refugees fleeing war and violence around the world are women and children. The United Nations has suggestions for offering help. Our global health expert, Dr. Callister, lists ways you can make a difference.